Scholarly Review of the Events in “Qalb al Siyar” till the Gracious Nativity of the Holy Prophet (SAW) - Sami ur Rahman; Hafiz Abdul Ghafoor (Journal of Islamic and Religious Studies, 2021)
So many books have been written on Sīrah since the 1st A.H. Different Sīrah writers have attempted to write books to pay tribute to the Holy Prophet (saw). Among these Sīrah writers, one is Gohar Khan Khattak, a prominent Pashto and Persian prose writer. Gohar Khan Khattak has written an enormous book in Pashto language on Sīrah, comprises about eight hundred pages. The theme of this book is the Sīrah of the Prophet (SAW), his lifestyle, and Ghazawāt. Gohar Khan Khattak has collected all kinds of narrations regarding the Sīrah. This study is an attempt to compare these narrations with authentic books of Sīrah, so that the narrations, till the birth of the Holy Prophet (SAW), mentioned in “Qalb al Siyar” may be analyzed practically. The study concludes that Khattak has no authentic source of Sīrah that is why many Ḍa’īf narrations are part of his book. Moreover, he has entered his opinions in sirah, which are not mentioned in authentic books of Sīrah and history.